Violet-blue emissions due to frequency up-conversion in Nd3+-doped fluoroindate glasses - Acioli, L. H.; Guo, J. T.; Araújo, Cid B. de; Messaddeq, Younes [UNESP]; Aegerter, M. A. (Elsevier, 1997)
We report the observation of intense frequency up-conversion in Nd3+-doped fluoroindate glasses pumped by the second harmonic of a cw mode-locked Nd: YAG laser. Mechanisms for generating the observed emissions are discussed.
Keywords: Blue-violet emission; Fluoroindate glasses; Rare-earth; Doping (additives); Frequencies; Glass; Neodymium; Pumping (laser); Second harmonic generation; Solid state lasers; Fluoroindate glass; Up conversion lasers; Violet blue emission; Light emission